Organic carbonyl compound electrode material, preparation method and application of organic carbonyl compound electrode material in lithium ion battery
By using organic carbonyl compound electrode materials containing nitrogen heterocycles in lithium-ion batteries, the problem of insufficient cycle life and rate performance of organic electrode materials is solved, high capacity and excellent electrochemical performance are achieved, and traditional small organic molecules are significantly improved Properties of the cathode material.
Patent Information
- Application Number
- CN202411327643.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The cycle life and rate performance of organic electrode materials in existing lithium-ion batteries is limited by high solubility and low conductivity, making it difficult to take into account the characteristics of high capacity, fast charging and discharge and long life.
Dipyridino[3′, 2′:5, 6; 2″, 3″:7, 8 ]Qionoxaline[2,3-i]dipyridino[3,2-a:2',3'-c]phenazine-10,21-diquinone (pyridine-phenazine-benzoquinone) as the positive electrode material , the coordinating of C=N double bond and C=O with lithium ions is used to improve the cycle stability and rate performance of the battery.
It significantly improves the cycle stability and rate performance of lithium-ion batteries, achieves high capacity and excellent electrochemical performance, the product preparation method is simple and efficient, the raw materials are green and cheap, the battery capacity remains 57% after 100 cycles, and the Coulomb efficiency is as high as 100%. , and exhibits high lithium storage reversibility at different current densities.
Smart Images

Figure CN119324226A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to an organic carbonyl compound electrode material, a preparation method and application thereof in lithium ion batteries. Background Art
[0002] The battery energy density of the current commercial lithium-ion battery system is difficult to further increase. The specific capacity of commonly used inorganic electrode materials is generally 100-200 mAh g -1 , while the specific capacity of graphite anode is as high as 400 mAh g -1 Compared with traditional inorganic electrode materials, organic molecules have the advantages of renewable resources, environmental friendliness, and highly designable structures. They are ideal candidate materials for the development of low-cost, high-efficiency, and environmentally friendly energy storage batteries. Among them, small organic molecules, with their rich active sites and high structural controllability, can maximize the use of their exposed lithium storage sites and activity, and have been a hot research direction in recent years. However, the high solubility and low conductivity of small organic molecules in organic electrolytes severely limit the cycle life and rate performance of organic electrode materials. Studies have found that expanding the π-conjugated structure can enhance the interaction between molecules and promote the orderly arrangement of organic molecules, which not only reduces solubility but also facilitates charge transfer, thereby improving cycle stability and rate performance. At present, structures with non-redox activity (such as benzene, naphthalene and other rigid structures) are usually used to expand the π-conjugated system, resulting in a decrease in theoretical capacity.
[0003] Therefore, how to rationally design organic electrode materials with high capacity, fast charging and discharging, and long life characteristics remains a very challenging problem. Summary of the invention
[0004] In order to take into account the problems of solubility inertia and conductivity of organic small molecules and improve capacity and rate performance, the present invention provides an organic carbonyl compound electrode material and a preparation method thereof, and applies it to positive electrode materials of lithium ion batteries. The present invention uses nitrogen-containing heterocycles with redox activity to expand the π conjugated system; wherein the nitrogen-containing heterocycles can provide active sites to improve specific capacity; the expanded π conjugated system can reduce the solubility of active molecules and improve electron / ion conduction, thereby improving cycle stability and rate performance. An organic carbonyl compound electrode material provided by the present invention is a new nitrogen-containing heterocycle hyperconjugated organic electrode material. The expanded N-heterocycle conjugated organic structure is conducive to improving the cycle stability and rate performance of the battery. The C=N double bond as a redox active site can provide additional capacity contribution, and the synergistic coordination of C=O and C=N with lithium ions realizes reversible storage of ions during charging and discharging, thereby showing higher capacity and excellent electrochemical performance.
[0005] To achieve the above object, the present invention provides an organic carbonyl compound electrode material, wherein the organic carbonyl compound electrode material is dipyrido[3′,2′:5,6;2″,3″:7,8]quinoxaline[2,3-i]dipyrido[3,2-a:2′,3′-c]phenazine-10,21-diquinone, having the following structural formula:
[0006] The pyridine-phenazine-benzoquinone organic electrode material of the present invention is obtained by a simple dehydration condensation reaction of 1,2,4,5-tetraamino-p-benzoquinone and 1,10-phenanthroline-5,6-dione, and its structural formula is shown in the formula:
[0007]
[0008] The present invention also provides a method for preparing the above-mentioned organic carbonyl compound electrode material, wherein the organic carbonyl compound electrode material is obtained by dehydration condensation reaction of 1,2,4,5-tetraaminobenzoquinone and 1,10-phenanthroline-5,6-dione.
[0009] Furthermore, the preparation method comprises the following synthesis steps:
[0010] Step 1: Under an inert atmosphere, add 1,10-phenanthroline-5,6-dione and 1,2,4,5-tetraaminobenzoquinone to acetic acid, and heat and stir to react;
[0011] Step 2: After the reaction is completed, wash, filter and dry to obtain the organic carbonyl compound electrode material.
[0012] Furthermore, in step 1, the molar ratio of 1,10-phenanthroline-5,6-dione to 1,2,4,5-tetraaminobenzoquinone is 2 to 3:1.
[0013] Furthermore, in step 1, the conditions for the heating and stirring reaction are: first stirring at room temperature for 30-60 minutes, then heating to 100-120° C. and stirring under reflux for 12-24 hours.
[0014] Furthermore, in step 1, the inert atmosphere is nitrogen or argon.
[0015] Furthermore, in step 2, the filtration is performed by washing three times with hot acetic acid, acetone and ethanol respectively.
[0016] The present invention also provides a use of the organic carbonyl compound electrode material as described above in a positive electrode material for a lithium ion battery.
[0017] Furthermore, the organic carbonyl compound electrode material, conductive carbon and cross-linking agent are ground into a slurry in an organic solvent, coated on an aluminum foil current collector, and vacuum dried at 60-80°C for 12-24h to form a positive electrode sheet; metallic lithium is used as the negative electrode, Celgrad is used as the separator, an electrolyte is added, and a button battery is assembled in an argon-filled glove box.
[0018] Furthermore, the conductive carbon material is a conductive slurry, the cross-linking agent is polyvinylidene fluoride (PVDF); the electrolyte is a lithium bis(trifluoromethylsulfonyl)imide solution (LiTFSI) with a concentration of 1-2M, and the solvent is ethylene glycol dimethyl ether (DME) and 1,3-dioxolane (DOL) in a volume ratio of 1:1-1:3.
[0019] The organic carbonyl compound electrode material is used as a positive electrode material in a lithium-ion battery. Due to the large conjugated system, it has good solubility inertness in the electrolyte and is conducive to electron transmission, thereby improving the cycle stability and rate performance of the battery. In addition, the multiple active sites (C=O and C=N) provide more redox active sites to coordinate with lithium ions, realize reversible lithium storage, and show a higher capacity.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention provides an organic electrode material of a nitrogen-containing heterocyclic carbonyl compound, wherein the organic carbonyl compound electrode material is dipyrido[3′,2′:5,6;2″,3″:7,8]quinoxaline[2,3-i]dipyrido[3,2-a:2′,3′-c]phenazine-10,21-diquinone, referred to as a pyridine-phenazine-diquinone compound. The organic carbonyl compound electrode material is obtained by a dehydration condensation reaction of 1,2,4,5-tetraaminobenzoquinone and 1,10-phenanthroline-5,6-dione. The organic electrode material is used as a positive electrode material in a lithium-ion battery. Since it contains a large conjugated system, it has good solubility inertness in the electrolyte and is conducive to electron transmission, thereby improving the cycle stability and rate performance of the battery. In addition, the multiple active sites (C=O and C=N) provide more redox active sites to coordinate with lithium ions, realize reversible lithium storage, and show a higher capacity.
[0022] 2. The larger π-conjugated system of the pyridine-phenazine-benzoquinone organic molecule of the present invention provides a stable molecular structure, and the introduction of nitrogen-containing heterocycles provides more active sites, thereby increasing the theoretical specific capacity. In addition, during the charge and discharge process, a large number of conjugated systems are beneficial to charge transfer, improve the lithium ion diffusion coefficient and electron conduction, and the extended π-conjugated system can reduce the solubility of active molecules and improve electron / ion conduction, thereby improving cycle stability and rate performance. At the same time, the lone pair of electrons in the C=N bond increases the redox activity of pyridine-phenazine-benzoquinone, thereby obtaining a higher cycle specific capacity and excellent rate performance in lithium-ion batteries. The synergistic coordination of C=O and C=N with lithium ions enables reversible storage of ions during the charge and discharge process, thereby exhibiting a higher capacity and excellent electrochemical performance.
[0023] 3. The pyridine-phenazine-benzoquinone organic small molecule positive electrode material of the present invention is prepared by a simple condensation reaction. The product preparation method is simple and efficient, with high yield. The raw materials used are green and cheap. When used as a positive electrode material in lithium-ion batteries, it shows extremely high capacity, cycle stability and rate performance, significantly improving the capacity of traditional organic small molecule positive electrode materials and having outstanding electrochemical performance. The lithium-ion battery prepared by using the pyridine-phenazine-benzoquinone organic electrode material obtained by the present invention has a high capacity, cycle stability and rate performance at 0.2Ag. -1 After 100 cycles, the capacity is 295 mAh g -1 , maintaining the initial capacity (506mAh g -1 ) of 57%, and the Coulombic efficiency is as high as 100%, showing extremely high capacity and cycle stability. -1 At a current density of 205 mAh g -1 It has extremely high rate performance; when the current density returns to 0.1A -1 When the battery capacity is still up to 398mAh g -1 , and has high lithium storage reversibility. The pyridine-phenazine-benzoquinone organic electrode material obtained by the present invention shows extremely high capacity density, stable cycle life and excellent rate performance as a positive electrode material of a lithium ion battery.
[0024] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0026] Figure 1Schematic diagram of the synthesis route of the pyridine-phenazine-benzoquinone organic electrode material obtained in the present invention;
[0027] Figure 2 This is a Fourier transform infrared spectrum of the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention;
[0028] Figure 3 The hydrogen and carbon nuclear magnetic resonance spectra of the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention;
[0029] Figure 4 This is a scanned photo of the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention;
[0030] Figure 5 The powder X-ray diffraction pattern of the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention;
[0031] Figure 6 This is a thermogravimetric analysis diagram of the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention;
[0032] Figure 7 The lithium ion battery prepared by using the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention has a high conductivity at 0.5 mV s -1 Lithium-ion battery cyclic voltammetry curve with scan rate;
[0033] Figure 8 The lithium ion battery prepared by using the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention is 0.2Ag -1 Lithium-ion battery charge and discharge curves with current density;
[0034] Fig. 9 The figure is a rate performance diagram of a lithium ion battery at different current densities, which is made of a lithium ion battery using the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention;
[0035] Fig.10 The cyclic voltammetry curves at different scan rates are for a lithium-ion battery made using the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.
[0037] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the reagents and materials used in the following examples can be obtained from commercial sources. The battery performance test in the following examples uses a BlueDian battery test system and an ADMORE electrochemical workstation.
[0038] Example 1
[0039] A method for preparing an organic carbonyl compound electrode material comprises the following steps:
[0040] Step 1: Under nitrogen atmosphere, 210 mg (10 mmol) of 1,10-phenanthroline-5,6-dione (McLean, purity 97%) and 80.08 mg (5 mmol) of 1,2,4,5-tetraaminobenzoquinone (McLean, purity 97%) were placed in 50 mL of acetic acid, and the reactant ratio ensured that 1,10-phenanthroline-5,6-dione was excessive in order to reduce the generation of by-products. Stir at room temperature for 30-60 minutes, then heat to 100-120°C and stir under reflux for 12-24 hours.
[0041] Step 2: After the reaction is completed, cool to room temperature, pour the reaction mixture into 200 mL of water, rinse three times with hot acetic acid, acetone and ethanol respectively, and vacuum dry the solid product at 70°C to obtain the target product, which is pyridine-phenazine-benzoquinone.
[0042] Example 2
[0043] A method for preparing an organic carbonyl compound electrode material comprises the following steps:
[0044] Step 1: Under nitrogen atmosphere, 252 mg (12 mmol) of 1,10-phenanthroline-5,6-dione (McLean, purity 97%) and 96.1 mg (6 mmol) of 1,2,4,5-tetraaminobenzoquinone (McLean, purity 97%) were placed in 80 mL of acetic acid, and the reactant ratio ensured that 1,10-phenanthroline-5,6-dione was excessive in order to reduce the generation of by-products. Stir at room temperature for 30-60 minutes, then heat to 100-120°C and stir under reflux for 12-24 hours.
[0045] Step 2: After the reaction is completed, cool to room temperature, pour the reaction mixture into 400 mL of water, rinse three times with hot acetic acid, acetone and ethanol respectively, and vacuum dry the solid product at 80°C to obtain the target product, which is pyridine-phenazine-benzoquinone.
[0046] Example 3
[0047] A method for preparing an organic carbonyl compound electrode material comprises the following steps:
[0048] Step 1: Under argon atmosphere, 315 mg (15 mmol) of 1,10-phenanthroline-5,6-dione (McLean, purity 97%) and 120.01 mg (7.5 mmol) of 1,2,4,5-tetraaminobenzoquinone (McLean, purity 97%) were placed in 100 mL of acetic acid, and the reactant ratio ensured that 1,10-phenanthroline-5,6-dione was excessive in order to reduce the generation of by-products. Stir at room temperature for 30-60 minutes, then heat to 100-120°C and stir under reflux for 12-24 hours.
[0049] Step 2: After the reaction is completed, cool to room temperature, pour the reaction mixture into 500 mL of water, rinse three times with hot acetic acid, acetone and ethanol respectively, and vacuum dry the obtained solid product at 60°C to obtain the target product, which is pyridine-phenazine-benzoquinone.
[0050] Figure 1 The schematic diagram of the synthesis route of the pyridine-phenazine-benzoquinone organic electrode material obtained in the present invention is shown. The product is prepared by simple dehydration condensation, the product preparation method is simple, the yield is high, and the raw materials used are green and cheap.
[0051] Figure 2 This is a Fourier transform infrared spectrum of the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention. Figure 2 It can be seen that: at 1648cm -1 and 1535cm -1 The stretching vibration peaks of C=O and C=N bonds in pyridine-phenazine-benzoquinone compounds are 1469 cm -1 、1356cm -1 and 708cm -1 They represent the stretching vibration peaks of C=C, CN and CH bonds, and the other peaks at 3313 cm -1 The -NH2 stretching vibration band in tetraaminobenzoquinone does not appear, indicating the synthesis of this compound.
[0052] Figure 3 The hydrogen and carbon nuclear magnetic resonance spectra of the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention are shown in FIG. Figure 3 It can be seen that pyridine-phenazine-benzoquinone is reacted with deuterated trifluoroacetic acid as solvent. 1 H NMR has three chemical environments of hydrogen at 10.58, 9.62, and 8.71 ppm. 13 C NMR has six chemical environments of carbon: 183.12, 152.45, 147.23, 142.69, 131.65, and 130.34 ppm.
[0053] Figure 4This is a scanned photo of the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention. Figure 4 It can be seen that pyridine-phenazine-benzoquinone is a microrod with a rough surface and a relatively large specific surface area, which is conducive to the expression of the electrochemical properties of pyridine-phenazine-benzoquinone.
[0054] Figure 5 This is the powder X-ray diffraction pattern of the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention. Figure 5 It can be seen that pyridine-phenazine-benzoquinone has obvious and sharp diffraction peaks, including 10.5°, 12.8°, 16.6°, 22.3°, 23.8°, 25.7°, and 28.2°, of which 28.2° is due to the π-π interaction between pyridine-phenazine-benzoquinone molecules.
[0055] Figure 6 This is a thermogravimetric analysis diagram of the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention. In order to analyze the thermal stability of the pyridine-phenazine-benzoquinone organic electrode material, this example performs thermogravimetric analysis (TG) under an argon atmosphere, and the test temperature range is 25-700°C, and the heating rate is 10°C / min. The results show that the material has good thermal stability below 550°C, which is beneficial to the manufacture and operation of lithium-ion batteries in various environments. The physicochemical properties of the pyridine-phenazine-benzoquinone organic electrode materials obtained in Example 2 and Example 3 are similar to those of the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1, and will not be repeated here.
[0056] Application Examples
[0057] The pyridine-phenazine-benzoquinone, conductive slurry and PVDF obtained in Example 1 were stirred in a shaker at a mass ratio of 6:3:1 to form a slurry with good dispersion, and then evenly coated on an aluminum foil current collector, and vacuum dried at 60-80°C for 12-24h to form a pole piece, the pole piece was used as the positive electrode, the metal lithium sheet was used as the negative electrode, the separator was a PP separator, and the electrolyte was a 1M lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) solution (self-prepared) containing ethylene glycol dimethyl ether (DME) and 1,3-dioxolane (DOL) (volume ratio 1:1 to 1:3), and assembled into a 2032 button battery in an argon-filled glove box, and the test voltage range was 1.0V-3.5V vs Li / Li + .
[0058] Figure 7 The pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention is used at 0.5 mV s -1 -2.5mVs -1Cyclic voltammetry curves of lithium-ion batteries at different scan rates. When the scan rate is increased, the position and shape of the redox peaks of the pyridine-phenazine-benzoquinone organic cathode material remain basically unchanged, indicating that the redox reaction of the pyridine-phenazine-benzoquinone organic cathode material is highly reversible, which is beneficial to the electrochemical performance of the battery. In addition, within the voltage range of 1.0-3.5V, the cyclic voltammetry curve of the battery shows three pairs of redox peaks, which are 2.97 / 3.15, 2.45 / 2.73 and 2.21 / 2.42V (relative to Li / Li + ), indicating that pyridine-phenazine-benzoquinone can utilize C=O and C=N groups to react with Li + The synergistic coordination effect realizes reversible storage of lithium ions.
[0059] Figure 8 The lithium ion battery prepared by using the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention is 0.2Ag -1 The charge and discharge curves of lithium-ion batteries under current density and different cycle numbers. The four-cycle charge and discharge curves show that their curve profiles are basically consistent, the specific capacity decays slowly, and they have a higher discharge platform. This further illustrates that the pyridine-phenazine-benzoquinone organic electrode material has excellent electrochemical properties.
[0060] Fig. 9 The lithium ion battery prepared by using the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention is 0.2Ag -1 Electrochemical cycle diagram of lithium-ion battery at current density. Fig. 9 It can be seen that at 0.2Ag -1 After 100 cycles, the capacity is 295 mAh g -1 , maintaining the initial capacity (506mAh g -1 ) of 57%, and the Coulombic efficiency is as high as 100%. It can be seen that pyridine-phenazine-benzoquinone organic electrode materials have high specific capacity and stable cycle life.
[0061] Fig.10 The figure is a graph showing the rate performance of a lithium-ion battery made of the pyridine-phenazine-benzoquinone organic electrode material obtained in Example 1 of the present invention at different current densities. Fig.10 It can be seen that at 0.1, 0.2, 0.3, 0.5, 1, 2, 3, 5 and 10Ag -1 At current densities of , the battery capacities are 445, 385, 328, 307, 287, 260, 234, 205 and 150 mAh g -1 When the current density returns to 0.1Ag -1 When the battery capacity is still up to 398mAh g -1, indicating that pyridine-phenazine-benzoquinone has a high reversibility of lithium storage. The electrochemical performance of lithium-ion batteries prepared with the pyridine-phenazine-benzoquinone organic electrode materials prepared in Examples 2 and 3 as the positive electrode materials of lithium-ion batteries is similar to the electrochemical performance of lithium-ion batteries prepared with the pyridine-phenazine-benzoquinone organic electrode materials prepared in Example 1 as the positive electrode materials of lithium-ion batteries, which will not be repeated here.
[0062] Therefore, the nitrogen-containing heterocyclic pyridine-phenazine-benzoquinone organic electrode material prepared by the present invention is used as a positive electrode material in a lithium-ion battery and exhibits good electrochemical performance.
[0063] In summary, the present invention provides an organic electrode material of a nitrogen-containing heterocyclic carbonyl compound, wherein the organic carbonyl compound electrode material is dipyrido[3′,2′:5,6;2″,3″:7,8]quinoxaline[2,3-i]dipyrido[3,2-a:2′,3′-c]phenazine-10,21-diquinone, referred to as a pyridine-phenazine-diquinone compound. The organic carbonyl compound electrode material is obtained by a dehydration condensation reaction of 1,2,4,5-tetraaminobenzoquinone and 1,10-phenanthroline-5,6-dione. The organic electrode material is used as a positive electrode material in a lithium-ion battery. Since it contains a large conjugated system, it has good solubility inertness in the electrolyte and is conducive to electron transmission, thereby improving the cycle stability and rate performance of the battery. In addition, the multiple active sites (C=O and C=N) provide more redox active sites to coordinate with lithium ions, realize reversible lithium storage, and exhibit a higher capacity.
[0064] The larger π conjugated system of the pyridine-phenazine-benzoquinone organic molecule of the present invention provides a stable molecular structure, and the introduction of nitrogen-containing heterocycles provides more active sites, thereby increasing the theoretical specific capacity. In addition, during the charge and discharge process, a large number of conjugated systems are beneficial to charge transfer, improve the lithium ion diffusion coefficient and electronic conduction, and the extended π conjugated system can reduce the solubility of active molecules and improve electronic / ion conduction, thereby improving cycle stability and rate performance. At the same time, the lone pair of electrons in the C=N bond increases the redox activity of the pyridine-phenazine-benzoquinone, thereby obtaining a higher cycle specific capacity and excellent rate performance in a lithium ion battery, and the synergistic coordination of C=O and C=N with lithium ions realizes reversible storage of ions during the charge and discharge process, thereby showing a higher capacity and excellent electrochemical performance.
[0065] In addition, the pyridine-phenazine-benzoquinone organic small molecule positive electrode material of the present invention is prepared by a simple condensation reaction. The product preparation method is simple and efficient with a high yield. The raw materials used are green and inexpensive. When used as a positive electrode material in lithium-ion batteries, it shows extremely high capacity, cycle stability and rate performance, significantly improving the capacity of traditional organic small molecule positive electrode materials and having outstanding electrochemical properties.
[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An organic carbonyl compound electrode material, characterized in that: The organic carbonyl compound electrode material is dipyrido[3′,2′:5,6;2″,3″:7,8]quinoxaline[2,3-i]dipyrido[3,2-a:2′,3′-c]phenazine-10,21-diquinone, having the following structural formula:
2. A method for preparing an organic carbonyl compound electrode material as claimed in claim 1, characterized in that: The organic carbonyl compound electrode material is obtained by dehydration condensation reaction of 1,2,4,5-tetraamino-p-benzoquinone and 1,10-phenanthroline-5,6-dione.
3. The preparation method according to claim 2, characterized in that: The following steps are involved: Step 1: Under an inert atmosphere, add 1,10-phenanthroline-5,6-dione and 1,2,4,5-tetraaminobenzoquinone to acetic acid, and heat and stir to react; Step 2: After the reaction is completed, wash, filter and dry to obtain the organic carbonyl compound electrode material.
4. The preparation method according to claim 3, characterized in that: In step 1, the molar ratio of 1,10-phenanthroline-5,6-dione to 1,2,4,5-tetraaminobenzoquinone is 2 to 3:
1.
5. The preparation method according to claim 3, characterized in that: In step 1, the conditions for the heating and stirring reaction are: first stirring at room temperature for 30-60 minutes, then heating to 100-120° C. and stirring under reflux for 12-24 hours.
6. The preparation method according to claim 3, characterized in that: In step 1, the inert atmosphere is nitrogen or argon.
7. The preparation method according to claim 3, characterized in that: In step 2, the filtration is performed by washing three times with hot acetic acid, acetone and ethanol respectively.
8. Use of the organic carbonyl compound electrode material as claimed in claim 1 in a positive electrode material for a lithium ion battery.
9. The use according to claim 8, characterized in that The organic carbonyl compound electrode material, conductive carbon and cross-linking agent are ground into slurry in an organic solvent, coated on an aluminum foil current collector, and vacuum dried at 60-80°C for 12-24h to form a positive electrode sheet; metallic lithium is used as the negative electrode, Celgrad is used as the separator, an electrolyte is added, and a button battery is assembled in an argon-filled glove box.
10. The use according to claim 9, characterized in that: The conductive carbon material is conductive slurry, the cross-linking agent is polyvinylidene fluoride; the electrolyte is a 1-2M lithium bis-trifluoromethylsulfonyl imide solution, and the solvent is ethylene glycol dimethyl ether and 1,3-dioxolane in a volume ratio of 1:1-1:3.
Citation Information
Patent Citations
5,7,12,14-tetranitrogen-6,13-pentacenequinone-based electrode material as well as preparation method and application thereof
CN108864104A
Diquinoxaline phenazine derivative and synthesis method and application thereof
CN109020982A
Polymer containing pyrazine-benzoquinone structure and application of polymer in lithium ion / aqueous zinc ion battery
CN114920930A
Self-charging electrochemical cell
CN117751475A
Cited By
Conjugate extended lithium-containing organic positive electrode material and preparation method and application thereof
CN120329544A
A conjugated extended lithium-containing organic positive electrode material and its preparation method and application
CN120329544B